455 The Changing Trends of Image Guided Biopsy of Small Renal Masses Before Intervention- an Analysis of European Multinational Prospective EuRECA Registry. (19th August 2022) - Chan, VWS; Keeley, F; Lagerveld, B; Breen, D; King, A; Nielsen, T; van Strijen, M; Garnon, J; Alcorn, D; Graumann, O; de Kerviler, E; Zondervan, P; et al.
Abstract: Aim: To evaluate the use of pre-cryoablation biopsy for small renal masses (SRMs) and the effects of increasing up take on histological results of treated SMRs. Method: From 2015 to 2019, patients with sporadic T1N0M0 SRMs undergoing percutaneous, laparoscopic or open cryoablation from 14 European institutions within the European Registry For Renal Cryoablation (EuRECA) were included for the retrospective analysis. Univariate and multivariate logistic models were used to evaluate the trends, histological results and the factors influencing use of pre-cryoablation biopsy. Results: 871 patients (Median [IQR] age, 69[14], 298 women) undergoing cryoablation were evaluated. The use of pre-cryoablation biopsy has significantly increased from 42% (65/156) in 2015 to 72% (88/122) in 2019 (p<0.001). Patients treated for a benign histology are significantly more likely to have presented later in the trend, where pre-cryoablation biopsy is more prevalent (OR: 0.64, 95% CI 0.51–0.81, p<0.001). Patients treated for undiagnosed histology are also significantly less likely to have presented in 2018 compared to 2016 (OR 0.31, 95% CI 0.10–0.97, p=0.044). Patients aged 70+ are less likely to be biopsies pre-cryoablation (p<0.05). R.E.N.A.L. nephrometry score of 10+ and a Charlson Comorbidity Index >1 are factors associated with lower likelihood to not have received a pre-cryoablation biopsy (p<0.05). Conclusion: An increased use of pre-cryoablation biopsy was observed and cryoablation patients treated with a benign histology is more likely to have presented in periods where pre-cryoablation biopsy is not as prevalent. Comparative studies are needed to draw definitive conclusions on the effect of pre-cryoablation biopsy on SRM treatments.